Effect of Channel Orientation and Rib Pitch-to-Height Ratio on Pressure Drop in a Rotating Square Channel with Ribs on Two Opposite Surfaces - Prabhu S. V.; Arora Neelabh; Vedula R. P. (International Journal of Rotating Machinery)
The effect of channel orientation and rib pitch-to-height ratio on the pressure drop distribution in a rib-roughened channel is an important issue in turbine blade cooling. The present investigation is a study of the overall pressure drop distribution in a square cross-sectioned channel, with rib turbulators, rotating about an axis normal to the free stream. The ribs are configured in a symmetric arrangement on two opposite surfaces with a rib angle of 90 ∘ to the mainstream flow. The study has been conducted for three Reynolds numbers, namely, 13 000, 17 000, and 22 000 with the rotation number varying from 0– 0.38 . Experiments have been carried out for various rib pitch-to-height ratios ( P/e ) with a constant rib height-to-hydraulic diameter ratio ( e/D ) of 0.1 . The test section in which the ribs are placed on the leading and trailing surfaces is considered as the base case ( <mtext>orientation angle</mtext>= 0 ∘ , Coriolis force vector normal to the ribbed surfaces). The channel is turned about its axis in steps of 15 ∘ to vary the orientation angle from 0 ∘ to 90 ∘ . The overall pressure drop does not change considerably under conditions of rotation for the base case. However, for the other cases tested, it is observed that the overall pressure drop increases with an increase in the rotation number for a given orientation angle and also increases with an increase in the orientation angle for a given rotation number. This change is attributed to the variation in the separation zone downstream of the ribs due to the presence of the Coriolis force—local pressure drop data is presented which supports this idea. At an orientation angle of 90 ∘ (ribs on the top and bottom surfaces, Coriolis force vector normal to the smooth surfaces), the overall pressure drop is observed to be maximum during rotation. The overall pressure drop for a case with a rib pitch-to-height ratio of 5 on both surfaces is found to be the highest among all the rib pitch-to-height ratios covered in this study with the maximum increase in the overall pressure drop being as high as five times the corresponding no-rotation case at the highest rotation number of 0.38 and 90 ∘ orientation angle.